STRAIN INVESTIGATIONS ON CALCITE MARBLES USING NEUTRON TIME-OF-FLIGHT DIFFRACTION - Scheffzük C.; Siegesmund S.; Koch A. (My University, 2004)
In order to describe and explain the effect of bowing of marble facade panels, neutron time-of-flight diffraction was applied to determine residual macro- and microstrain on the calcite mineral phase. The measurements were combined with investigations of the crystallographic preferred orientation (texture) measurements by neutron diffraction, macroscopic measuring of the bowing on marble building stones, as well as microfabric analyses. Three samples were investigated to explain the bowing effect: a fresh broken sample, a good conditioned facade panel and a strongly deformed facade panel. Residual intracrystalline strain was detected in all investigated samples, which differed in the degree of bowing. For the first time, the preferred orientation and the residual strain were found to be related. The results show that different strain magnitudes are reflected by residual strains, which differ significantly in magnitude and direction. Furthermore, different Bragg peak widths have been detected as an indication of microscopic strain. The observed residual strain values in the samples are related with the grain shape and texture properties.
Keywords: Calcite; Marble; Neutron diffraction; Strain and stress; Texture